Induction of Cryptic and Bioactive Metabolites through Natural Dietary Components in an Endophytic Fungus Colletotrichum gloeosporioides (Penz.) Sacc. - Sharma, Vijay K.; Kumar, Jitendra; Singh, Dheeraj K.; Mishra, Ashish; Verma, Satish K.; Gond, Surendra K.; Kumar, Anuj; Singh, Namrata; Kharwar, Ravindra N. (Frontiers in Microbiology, 2017)
Grape skin and turmeric extracts having the major components resveratrol and curcumin respectively, were used for the induction of cryptic and bioactive metabolites in an endophytic fungus Colletotrichum gloeosporioides isolated from Syzygium cumini. The increase in total amount of crude compounds in grape skin and turmeric extract treated cultures was 272.48% and 174.32% respectively, compared to the untreated control. Among six human pathogenic bacteria tested, the maximum inhibitory activity was found against Aeromonas hydrophila IMS/GN11 while no inhibitory activity was observed against Enterococcus faecalis IMS/GN7. The crude compounds derived from turmeric extract treated cultures showed the highest DPPH free radicals scavenging activity (86.46% inhibition) followed by compounds from grape skin treated cultures (11.80% inhibition) and the control cultures (1.92% inhibition). Both the treatments significantly (p ≤ 0.05) increased the antibacterial and antioxidant activities of crude metabolites compared to the control. HPLC profiling of crude compounds derived from grape skin and turmeric extract treated cultures revealed the presence of additional 20 and 14 cryptic compounds respectively, compared to the control. These findings advocate the future use of such dietary components in induced production of cryptic and bioactive metabolites.